Preparation method of copper foil with double-peak heterogeneous grain structure

By adding compound additives and segmented rapid annealing treatment in the preparation process of ultra-thin copper foil, a bimodal heterograin structure is formed, which solves the problem of balance between strength and elongation of copper foil, and achieves high-performance copper foil preparation.

CN119800458APending Publication Date: 2025-04-11HUBEI ENG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036778.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing ultra-thin copper foil is difficult to achieve a balance between strength and elongation. Although grain refinement can increase strength, it will lead to a decrease in elongation.

Method used

The DC electrodeposition method is used to add specific compound additives, and the copper foil is processed by segmented rapid annealing to form a copper foil with a bimodal heterograin structure.

Benefits of technology

The copper foil has achieved excellent performance in yield strength, ultimate tensile strength and elongation, and has high yield strength, high ultimate tensile strength and high elongation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800458A_ABST
    Figure CN119800458A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper foil with a double-peak heterogeneous grain structure, which comprises the following steps: S1, preparing a basic electrolyte, adding the prepared basic electrolyte into an industrial electrolytic cell, and heating the basic electrolyte; and S2, adding the compound additive into the industrial electrolytic cell, and fully mixing the compound additive with the basic electrolyte. According to the method, the compound additive is added, the components in the compound additive have different hydrolysis degrees, the grain generation mechanism in the electrodeposition process can be inhibited, and an original double-peak grain microstructure is reserved while internal stress is removed by means of a segmented rapid annealing method. In the stretching process of the bimodal heterogeneous ultrathin copper foil, a large amount of geometric necessary dislocations at a crystal interface are promoted to be accumulated through formation of a strain gradient at the fine / coarsened nanocrystalline interface, so that the ultrathin copper foil of the type shows an excellent synergistic effect and has high yield strength, high ultimate tensile strength and high extensibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of copper foil, and in particular to a method for preparing copper foil with a bimodal heterogeneous grain structure. Background Art

[0002] With the rapid development of the lithium-ion battery industry, the high energy density design of lithium-ion batteries has put forward higher requirements on the strength and elongation of ultra-thin copper foil used as anode collector. However, since pure metal materials cannot improve their strength and elongation through precipitation phase strengthening and other means, ultra-thin copper foil still faces major obstacles in the dilemma of balancing strength and elongation.

[0003] At present, grain refinement is the only traditional method to strengthen pure metals without adding foreign elements. For example, the tensile strength of electrolytic copper foil can be significantly improved by grain refinement. Although the grains of copper foil can be further refined by introducing new specific additive pairs, which can promote the improvement of the ultimate tensile strength of copper foil, the elongation will drop sharply. Therefore, grain refinement can never break the trade-off between strength and elongation, which is attributed to the fact that the strength enhancement of copper foil is achieved by a large number of grain boundaries blocking the movement of dislocations. However, the smaller grain size leads to the inability to accumulate more dislocations within the grains, which leads to a significant reduction in the plasticity and work hardening ability of the copper foil, resulting in lower elongation. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned shortcomings and provide a method for preparing a copper foil with a bimodal heterogeneous grain structure. By adopting a direct current electrodeposition method, through specific compound additives and post-heat treatment parameters, a bimodal structure copper foil with a coarse and fine nano-grain heterogeneous structure is designed, which is suitable for large-scale production.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a copper foil with a bimodal heterogeneous grain structure, comprising the following steps:

[0006] S1. Prepare a basic electrolyte, add the prepared basic electrolyte into an industrial electrolytic cell, and heat the basic electrolyte;

[0007] S2. Add the compound additive into the industrial electrolytic cell and mix it with the basic electrolyte thoroughly;

[0008] S3, passing direct current into the industrial electrolytic cell for electrodeposition;

[0009] S4, the cathode roller continuously rotates to continuously peel off and roll up the copper foil to form a rolled copper foil, and then passes through a surface treatment machine for anti-oxidation treatment;

[0010] S5. Performing post-heat treatment on the copper foil after the anti-oxidation treatment, placing the copper foil in an annealing furnace, treating the copper foil by a segmented rapid annealing method, and then slowly cooling the annealed copper foil to room temperature.

[0011] Furthermore, the compound additives described in S2 include 20-30 ppm gelatin, 30-60 ppm polypropylene glycol and a compounding agent in terms of mass concentration.

[0012] Furthermore, the compounding agent comprises two or more of 10-40 ppm sodium polydisulfide propane sulfonate, 25-75 ppm sodium mercaptoimidazole propane sulfonate, 15-45 ppm sodium alcoholthiopropane sulfonate and 15-85 ppm sodium N-(3-sulfopropyl)-saccharin in mass concentration.

[0013] Furthermore, in S5, the segmented rapid annealing method comprises the following steps:

[0014] In the first stage, the temperature in the annealing furnace is raised to 140-200°C at a heating rate of 5-60°C / min and kept at this temperature for 0.5-2h;

[0015] In the second stage, after the first stage of heat preservation is completed, the temperature is increased to 250°C at a rate of 5-10°C / min and maintained at this temperature for 6-72h.

[0016] Furthermore, the basic electrolyte is prepared from deionized water, copper sulfate pentahydrate, sodium chloride and concentrated sulfuric acid, the copper ion concentration is 60-80 g / L, and the chloride ion concentration is 30-50 mg / L.

[0017] Furthermore, in S3, the parameters used for electrodeposition are a current density of 40-60 A / dm 2 , the deposition time is 160-180s.

[0018] Furthermore, in the step S1, the temperature of the basic electrolyte is raised to 60°C.

[0019] Furthermore, in S2, an air blowing device and an ultrasonic device are used to fully mix the compound additive with the basic electrolyte.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adds a compound additive, and the components in the compound additive have different hydrolysis degrees, which can inhibit the grain generation mechanism in the electrodeposition process, and use a segmented rapid annealing method to remove internal stress while retaining the original bimodal grain microstructure. During the stretching process of the bimodal heterogeneous ultra-thin copper foil, the formation of a strain gradient at the fine / coarsening nanocrystalline interface promotes the accumulation of a large number of geometrically necessary dislocations at the crystal interface, thereby achieving this type of ultra-thin copper foil exhibiting an excellent synergistic effect, with high yield strength, high ultimate tensile strength and high elongation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0023] Figure 1 This is the ESBD diagram of the copper foil prepared in Example 2 of the present invention.

[0024] Figure 2 This is the ESBD diagram of the copper foil prepared in Comparative Example 1 of the present invention.

[0025] Figure 3 This is the ESBD diagram of the copper foil prepared in Comparative Example 2 of the present invention.

[0026] Figure 4 This is the ESBD diagram of the copper foil prepared in Comparative Example 3 of the present invention.

[0027] Figure 5 The tensile stress-strain curves of the copper foils prepared in Example 2 of the present invention and Comparative Examples 1-3 are shown. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0029] Embodiment 1:

[0030] A method for preparing a copper foil having a bimodal heterogeneous grain structure comprises the following steps:

[0031] S1. Prepare a basic electrolyte, which is prepared from deionized water, copper sulfate pentahydrate, sodium chloride and concentrated sulfuric acid, with a copper ion concentration of 60 g / L and a chloride ion concentration of 30 mg / L. Add the prepared basic electrolyte into an industrial electrolytic cell, with a pH value of the electrolyte not less than 2, and heat the basic electrolyte to 60° C.;

[0032] S2. Adding compound additives into the industrial electrolytic cell, using an air blowing device and an ultrasonic device to fully mix the compound additives with the basic electrolyte, the compound additives including 20 ppm gelatin, 30 ppm polypropylene glycol and compounding agent according to mass concentration;

[0033] The compounding agent comprises 40 ppm sodium polydisulfide propane sulfonate, 75 ppm sodium mercaptoimidazole propane sulfonate, 45 ppm sodium alcoholthiopropane sulfonate and 15 ppm N-(3-sulfopropyl)-saccharin sodium salt in terms of mass concentration;

[0034] S3. Direct current is introduced into the industrial electrolytic cell for electrodeposition. The parameters used for electrodeposition are: current density of 40A / dm 2 , the deposition time is 180s;

[0035] S4, the cathode roller continuously rotates to continuously peel off and roll up the copper foil to form a rolled copper foil, and then passes through a surface treatment machine for anti-oxidation treatment;

[0036] S5, performing post-heat treatment on the copper foil after the anti-oxidation treatment, placing the copper foil in an annealing furnace, and treating the copper foil by a segmented rapid annealing method, wherein the segmented rapid annealing method comprises the following steps:

[0037] In the first stage, the temperature in the annealing furnace is raised to 140°C at a heating rate of 5°C / min and kept at this temperature for 0.5h. In the second stage, after the first stage of heat preservation, the temperature is raised to 250°C at a heating rate of 5°C / min and kept at this temperature for 6h.

[0038] The annealed copper foil is then slowly cooled to room temperature.

[0039] The obtained sample was tested and its yield strength was 581.3 MPa, the ultimate tensile strength was 622.1 MPa and the elongation was 5.8%.

[0040] Embodiment 2:

[0041] A method for preparing a copper foil having a bimodal heterogeneous grain structure comprises the following steps:

[0042] S1. Prepare a basic electrolyte, which is prepared from deionized water, copper sulfate pentahydrate, sodium chloride and concentrated sulfuric acid, with a copper ion concentration of 70 g / L and a chloride ion concentration of 40 mg / L. Add the prepared basic electrolyte into an industrial electrolytic cell and heat the basic electrolyte to 60° C.;

[0043] S2. Adding compound additives into the industrial electrolytic cell, using an air blowing device and an ultrasonic device to fully mix the compound additives with the basic electrolyte, the compound additives including 25 ppm gelatin, 45 ppm polypropylene glycol and compounding agent according to mass concentration;

[0044] The compounding agent comprises 25 ppm sodium polydisulfide propane sulfonate, 50 ppm sodium mercaptoimidazole propane sulfonate and 30 ppm sodium alcoholthiopropane sulfonate in terms of mass concentration;

[0045] S3. Direct current is introduced into the industrial electrolytic cell for electrodeposition. The parameters used for electrodeposition are: current density of 50A / dm 2 , deposition time is 170s;

[0046] S4, the cathode roller continuously rotates to continuously peel off and roll up the copper foil to form a rolled copper foil, and then passes through a surface treatment machine for anti-oxidation treatment;

[0047] S5, performing post-heat treatment on the copper foil after the anti-oxidation treatment, placing the copper foil in an annealing furnace, and treating the copper foil by a segmented rapid annealing method, wherein the segmented rapid annealing method comprises the following steps:

[0048] In the first stage, the temperature in the annealing furnace was raised to 170°C at a heating rate of 30°C / min and kept at this temperature for 1.5 hours. In the second stage, after the first stage of heat preservation, the temperature was raised to 250°C at a heating rate of 8°C / min and kept at this temperature for 39 hours.

[0049] The annealed copper foil is then slowly cooled to room temperature.

[0050] The obtained sample was tested and its yield strength was 593.2 MPa, ultimate tensile strength was 617.8 MPa and elongation was 5.6%.

[0051] Embodiment 3:

[0052] A method for preparing a copper foil having a bimodal heterogeneous grain structure comprises the following steps:

[0053] S1. Prepare a basic electrolyte, which is prepared from deionized water, copper sulfate pentahydrate, sodium chloride and concentrated sulfuric acid, with a copper ion concentration of 80 g / L and a chloride ion concentration of 50 mg / L. Add the prepared basic electrolyte into an industrial electrolytic cell and heat the basic electrolyte to 60° C.;

[0054] S2. Adding compound additives into the industrial electrolytic cell, using an air blowing device and an ultrasonic device to fully mix the compound additives with the basic electrolyte, the compound additives including 30 ppm gelatin, 60 ppm polypropylene glycol and compounding agent according to mass concentration;

[0055] The compounding agent comprises 40ppm sodium polydisulfide propane sulfonate, 75ppm sodium mercaptoimidazole propane sulfonate, and 45ppm sodium alcoholthiopropane sulfonate according to mass concentration;

[0056] S3. Direct current is introduced into the industrial electrolytic cell for electrodeposition. The parameters used for electrodeposition are: current density of 60A / dm 2 , deposition time is 160s;

[0057] S4, the cathode roller continuously rotates to continuously peel off and roll up the copper foil to form a rolled copper foil, and then passes through a surface treatment machine for anti-oxidation treatment;

[0058] S5, performing post-heat treatment on the copper foil after the anti-oxidation treatment, placing the copper foil in an annealing furnace, and treating the copper foil by a segmented rapid annealing method, wherein the segmented rapid annealing method comprises the following steps:

[0059] In the first stage, the temperature in the annealing furnace is raised to 200°C at a heating rate of 60°C / min and kept at this temperature for 2 hours. In the second stage, after the first stage of heat preservation, the temperature is raised to 250°C at a heating rate of 10°C / min and kept at this temperature for 72 hours.

[0060] The annealed copper foil is then slowly cooled to room temperature.

[0061] The obtained sample was tested and its yield strength was 589.5 MPa, the ultimate tensile strength was 621.1 MPa and the elongation was 5.7%.

[0062] Figure 1 This is the ESBD diagram of the copper foil prepared in Example 2. Taking the parameters of Example 2 as the standard, a comparative example is set:

[0063] Comparative Example 1: The difference between this comparative example and Example 2 is that the compound additive is added and the copper foil is treated by a conventional annealing method. The EBSD image of the copper foil obtained is as follows: Figure 2 shown.

[0064] Comparative Example 2: The difference between this comparative example and Example 2 is that the composite additive proposed in the present application is not used, and conventional additives are used, such as adding sodium polydisulfide propane sulfonate alone, and the copper foil is treated by the segmented rapid annealing method proposed in the present application. The EBSD image of the obtained copper foil is as follows: Figure 3 shown.

[0065] Comparative Example 3: The difference between this comparative example and Example 2 is that the composite additive proposed in this application is not used, and conventional additives are used, such as adding sodium polydisulfide propane sulfonate alone, and the copper foil is treated by a conventional annealing method. The EBSD image of the obtained copper foil is as follows: Figure 4 shown.

[0066] The copper foils prepared in Example 2 and Comparative Examples 1-3 were subjected to tensile stress-strain tests at room temperature. Figure 5 As shown, Figure 5 1 is the copper foil prepared in Example 2, 2 is the copper foil prepared in Comparative Example 1, 3 is the copper foil prepared in Comparative Example 2; and 4 is the copper foil prepared in Comparative Example 3.

[0067] Combination Figure 1-Figure 5 Through the tensile test results, it was found that the bimodal heterogeneous ultra-thin copper foil exhibited excellent synergistic effect, which was mainly attributed to the bimodal heterogeneous structure leading to the formation of strain gradient at the fine / coarsened nanocrystalline interface of the copper foil during the stretching process. In addition, the high-density geometric necessary dislocations accumulated at the interface can also effectively inhibit the strain concentration in the subsequent plastic deformation, which helps to maintain the strengthening effect induced by high heterogeneous deformation. The prepared bimodal heterogeneous grain structure ultra-thin copper foil has ideal yield strength and elongation. The use of compound additives and the segmented rapid annealing method have a mutually coordinated effect, which can effectively improve the performance of the prepared copper foil.

[0068] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a copper foil having a bimodal heterogeneous grain structure, characterized in that: The steps include: S1. Prepare a basic electrolyte, add the prepared basic electrolyte into an industrial electrolytic cell, and heat the basic electrolyte; S2. Add the compound additive into the industrial electrolytic cell and mix it with the basic electrolyte thoroughly; S3, passing direct current into the industrial electrolytic cell for electrodeposition; S4, the cathode roller continuously rotates to continuously peel off and roll up the copper foil to form a rolled copper foil, and then passes through a surface treatment machine for anti-oxidation treatment; S5. Performing post-heat treatment on the copper foil after the anti-oxidation treatment, placing the copper foil in an annealing furnace, treating the copper foil by a segmented rapid annealing method, and then slowly cooling the annealed copper foil to room temperature.

2. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 1, characterized in that: The compound additives described in S2 include 20-30 ppm gelatin, 30-60 ppm polypropylene glycol and a compounding agent in terms of mass concentration.

3. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 2, characterized in that: The compounding agent comprises two or more of 10-40 ppm sodium polydisulfide propane sulfonate, 25-75 ppm sodium mercaptoimidazole propane sulfonate, 15-45 ppm sodium alcoholthiopropane sulfonate and 15-85 ppm sodium N-(3-sulfopropyl)-saccharin in terms of mass concentration.

4. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 1, characterized in that: In said S5, the segmented rapid annealing method comprises the following steps: In the first stage, the temperature in the annealing furnace is raised to 140-200°C at a heating rate of 5-60°C / min and kept at this temperature for 0.5-2h; In the second stage, after the first stage of heat preservation is completed, the temperature is increased to 250°C at a rate of 5-10°C / min and maintained at this temperature for 6-72h.

5. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 4, characterized in that: The basic electrolyte is prepared from deionized water, copper sulfate pentahydrate, sodium chloride and concentrated sulfuric acid, with a copper ion concentration of 60-80 g / L and a chloride ion concentration of 30-50 mg / L.

6. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 1, characterized in that: In S3, the parameters used for electrodeposition are current density of 40-60A / dm 2 , deposition time is 160-180s.

7. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 1, characterized in that: In S1, the temperature of the base electrolyte is raised to 60°C.

8. The method for preparing a copper foil having a bimodal heterogeneous grain structure according to claim 1, characterized in that: In S2, the compounded additive and the basic electrolyte are fully mixed using an air blowing device and an ultrasonic device.